What Affects Teachers’ Use of Technology: Teachers’ Beliefs Regarding Technology, Teachers’ Technological Skills, or Available Sources of Support? - Roman Yavich; Nitza Davidovitch (Education Sciences)
Many studies have examined teachers’ use of technology, but not many have examined what factors promote such use. The current study examines the effect of several factors on use of technology by teachers. A questionnaire on this topic was given to 120 male and female teachers from Israel. It was found that teachers’ beliefs on the effectiveness of use of technology in education, as well as support for such use from parents of school students, promotes teachers’ use of technology in education. Teachers’ technological knowledge and skills, support from the school management and from Education Ministry supervisors, and the availability of technological support were not found to promote teachers’ use of technology in education. Conducting programs and workshops that will educate teachers on the usefulness of technology in education and promote parent–teacher cooperation is recommended. The study may greatly help to promote the use of technology in teaching and education, which may greatly improve student learning.